2018
DOI: 10.1093/rheumatology/key222
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-18 in muscle tissue of patients with polymyositis or dermatomyositis and effects of conventional immunosuppressive treatment

Abstract: IL-18 is highly expressed in muscle tissue in the context of inflammatory myopathies and based on its plausible effector functions could provide a novel therapeutic target in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…51 IL-18 may be also involved in regulating intramuscular lipid metabolism and hypertriglyceridemia, controlling local access to energy stores. 52,53 While high intramuscular expression of IL-18 has been reported in inflammatory diseases and myopathies, 54,55 the IL-18 concentrations did not appear to follow the trends in the Oil Red O staining (Figure 8). Taken together, perhaps the effects and interactions of IL-1β, IL-18, and IFNγ prolonged upregulation of satellite cell proliferation combined with regulation of injury lipogenesis and inflammation contributed to the increased contraction force.…”
Section: Discussionmentioning
confidence: 89%
“…51 IL-18 may be also involved in regulating intramuscular lipid metabolism and hypertriglyceridemia, controlling local access to energy stores. 52,53 While high intramuscular expression of IL-18 has been reported in inflammatory diseases and myopathies, 54,55 the IL-18 concentrations did not appear to follow the trends in the Oil Red O staining (Figure 8). Taken together, perhaps the effects and interactions of IL-1β, IL-18, and IFNγ prolonged upregulation of satellite cell proliferation combined with regulation of injury lipogenesis and inflammation contributed to the increased contraction force.…”
Section: Discussionmentioning
confidence: 89%
“…Under the action of IL18, these two subunits show a high affinity and form a complex, thus activating intracellular signaling pathways, such as NF-κB and AP-1 transcription factors ( Yasuda et al, 2019 ). Previous studies have shown that an increased serum IL18 correlated with ILD in DM ( Gono et al, 2010 ), and that IL18 was expressed in muscle infiltrating cells of patients with myositis ( Helmers et al, 2018 ). Moreover, endothelial cells, smooth muscle cells and CD8 + cells expressed a high content of IL18R ( Tucci et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 has previously been identified to be elevated in DM muscle biopsies, and expression decreases with immunosuppressive treatment for the muscle disease ( 22 ). In the skin, activation of IL-18 has been identified as important in other autoimmune and inflammatory skin diseases such as vitiligo, atopic dermatitis, and alopecia areata ( 23 ).…”
Section: Discussionmentioning
confidence: 99%